Apocalypse now redux [videorecording (DVD)] - Coppola, Francis Ford, 1939-; Sheen, Martin; Brando, Marlon; Duvall, Robert; Forrest, Frederic; Hall, Albert; Bottoms, Sam, 1955-2008; Fishburne, Laurence, III, 1961-; Hopper, Dennis, 1936-2010; Conrad, Joseph, 1857-1924 (Paramount, 2001)
A United States Army officer/trained assassin is sent into the depths of a southeast Asian jungle to seek out a renegade colonel and terminate his command during the Vietnam War.